The Believer in One Almighty God and Digital Technology: Case Study on Paguyuban Budaya Bangsa Pusat Kebumen - Priyono, Dedi; Novita Al Ihyak Dieni (Indonesian Journal of Multidisciplinary Educational Research, 2024)
Digital technology has become a core part of daily life, impacting communication, work, and interaction. This shift poses challenges for maintaining spiritual values, especially as it affects how religious beliefs and practices are integrated into modern culture. This is a challenge for believers to be able to accept the development of digital technology by not changing the sacredness of the guidance. This research investigates how members of Paguyuban Budaya Bangsa (PBB), a belief organization in Wonokriyo Village in Kebumen, navigate these challenges, exploring the influence of digital technology on their spiritual teachings, their efforts to preserve traditional doctrines like "maca alam, maca kahanan," and the limitations they encounter in balancing tradition with modern advancements. This case study was conducted using a qualitative research method. Data collection techniques were carried out by interviewing organization administrators, elders, and the younger generation of Paguyuban Budaya Bangsa. The results showed that the guidance of believers in this group is related to the way their members interact with digital technology such as the meaning contained in the guidance of "maca alam, maca kahanan" where Paguyuban Budaya Bangsa uses computers to adapt to the times and the sustainability of the organization. In addition, the believers also use mobile phones as a tool of communication to interact with administrators and other members. The believers still maintain guidance in the use of digital technology, which reflects the balance between tradition and modernity.